Enzymatic Production of Fish Protein Hydrolysates in A Pilot Plant Scale - Martosuyono, Pujoyuwono; Fawzya, Yusro Nuri; Patantis, Gintung; Sugiyono, Sugiyono (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
Protease enzyme produced from Bacillus sp was employed to hydrolyze fish protein hydrolysates (FPH) under controlled conditions at a batch-pilot plant scale-process. Thirty kilograms of fish meat was mincedand mixed with 60 liters of water in 100 liters stainless steel vessel and 20,000 units of protease enzyme was added per kg of fish. Hydrolysis of fish was carried out at 55 oC for 6 hours. Multi stage of filtration were done to separate the FPH from unhydrolized fish residue. Mass balance were carried out to determine the rate of hydrolysis and yields. W ithout pH adjustment, 80% of substrate hydrolyzed could be achieved in 6 hour at 55 Â°C. Three kinds of products were recovered from the process, i.e solid residue, liquid FPH as filtration product, and spray dried FPH. Hydrolysis of 30 kg of fish meat substrate producing 1.7-2.0 kg of unhydrolyzed residue and 70 L of liquid FPH. Afterspray drying process of liquid FPH, 13 kg of FPH powder was recovered. The proximate and amino acid analysis of spray dried FPH showed that the FPH containing 20% of protein, rich in amino acids especially lysine and leucineand the residue still had 85,36% of protein (dry basis) that could be utilized for other purpose.